ANALISIS PERTANGGUNGJAWABAN PIDANA TERHADAP PELAKU EKSIBISIONISME BERDASARKAN HUKUM PIDANA INDONESIA - Hanaura Seyla Wahyudi; Emmilia Rusdiana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Exhibitionism is the conduct of intentionally exposing sexual organs to another person without consent to obtain sexual gratification or to create a sexualized situation. In Indonesian criminal law, this conduct intersects with offences against decency, pornography, electronic information, and sexual violence. This normative legal research uses statutory and conceptual approaches to examine the qualification of exhibitionism and the criminal liability of its perpetrators. The analysis shows that exhibitionism may be charged under Article 281 of the former Criminal Code for acts committed before 2 January 2026, Article 406 of the National Criminal Code, the Pornography Law, the ITE Law, and the Sexual Violence Crime Law, depending on the mode of conduct. Criminal liability remains subject to intent, unlawfulness, capacity, and mental condition.